Factors influencing the outcomes of online agricultural land lease auctions: Evidence from Ukraine - Myrna, Olena; Justus Liebig University Giessen (My University, 2023)
Ukraine has large and productive agricultural areas that could attract significant volumes of investment. However, this has long been impeded by the lack of a well-functioning transparent free market to sell and rent privately and publicly-owned land. In addition, the country and its land market were severely affected by Russia’s 2022 invasion, which led to a sharp economic decline and made significant areas unavailable. Nevertheless, Ukraine is likely to remain one of the world’s leading agriculture producers with significant agricultural production and export volumes, and will need to manage farmland efficiently. Ukraine’s land market formed as the country began transforming itself from a centrally planned economy to a market economy in the 1990s. During the first three decades of the transition, 75% of all agricultural land has been privatized, and the rest (or approximately 10.5 million hectares (ha)) remain state-owned. Mandatory ascending-price traditional land auctions were introduced in 2012 to remove the barriers to successful investing, and to facilitate the transfer of rental rights for state-owned agricultural land from the state to private holdings. The auctions, however, lacked transparency and efficiency. To eliminate corruption in land governance and to increase land use efficiency, a pilot project to rent out state-owned agricultural land via online auctions was launched in late 2018. The results of online auctions were publicly disclosed. They became an important source of pricing data available to all market participants. This online auction mechanism was planned to be employed in the future to rent out and sell publicly and privately-owned land. Before the online auction project began, land market research focused mainly on the emergence and development of the agricultural land market in Ukraine after the dissolution of the Soviet Union, land reforms, privatization, and distribution. Studies also focused on land market efficiency, equity, and productivity during and after the land reforms were implemented, as well as the role of large agricultural producers that were thought to exercise some market power. After the online auction data became available, several papers investigated issues related to land price formation. However, there has been no extensive research on factors that influence land auction outcomes, such as the probability of the plot being rented (i.e. auction success) and the size of the winning bid (i.e. rental rates). This thesis bridges this research gap, comprehensively analyses land auction outcomes, and determines which factors impact them the most. It begins with an investigation of how competition, active bidding, auction design characteristics, and farmland-specific properties influence auction outcomes, employing a mixed-effects model with sample selection. It then explores the occurrence of very small winning bid amounts in the auctions, and factors that can explain bidding errors, using (heteroscedastic) probit models. Later, it investigates if, over the first year of the project’s implementation, regional land management agencies were able to build a positive reputation among agricultural tenants, who could observe the publicly disclosed information about all previous auction outcomes. For this purpose, it uses multiple regression and probit models, a Heckman model with sample selection, and mediation analysis. The results of the thesis show that competition has the greatest influence on auction outcomes: A higher number of bidders and more active bidding lead to a significantly greater probability of auction success and higher rental rates. Bidders that face low competition are likely to bid below their true valuations. They are also likely to underbid if they have an insufficient amount of time to place a subsequent bid, if bid increments are too small, or if entry fees are cumbersome. Lessors with a better reputation may be associated with a greater probability of future transaction success and a substantial price premium. However, reputation plays an especially important role in auctions that are not very competitive. Trustworthy lessors tend to optimize the amount of effort and preparation costs in the longer term. Land auctions’ efficiency and revenues may be improved if more bidders are invited and a more competitive bidding process is facilitated. More bidders will participate if auction design parameters, like reserve price, bid increments, and entry fee amounts, are optimized. Potential tenants may adjust their willingness to pay in response to information about the positive or negative reputation of lessors. If they already have a good reputation, lessors may optimize the amount of effort they exert in the long term. If their reputation needs improvement, they may consider addressing this by investing more in preparing plots for rent.
Keywords: agricultural land market; land privatization; online auctions; auction outcomes; agricultural land rental prices; competition; bidding behaviour; reputation; ddc:330; ddc:333.7